Inhibition of lysosomal Ca2+ signalling disrupts dendritic spine structure and impairs wound healing in neurons - Zahid Padamsey; Lindsay McGuinness; Nigel J. Emptage (Communicative & Integrative Biology, 2017)
A growing body of evidence suggests that lysosomes, which have traditionally been regarded as degradative organelles, can function as Ca2+ stores, regulated by the second messenger nicotinic acid adenine dinucleotide phosphate (NAADP). We previously demonstrated that in hippocampal pyramidal neurons, activity-dependent Ca2+ release from these stores triggers fusion of the lysosome with the plasma membrane. We found that the physiological role of this Ca2+-dependent fusion was to maintain the long-term structural enlargement of dendritic spines induced by synaptic activity. Here, we examined the pathophysiological consequences of lysosomal dysfunction in hippocampal pyramidal neurons by chronically inhibiting lysosomal Ca2+ signalling using the NAADP antagonist, NED-19. We found that within just 20 hours, inhibition of lysosomal function led to a profound intracellular accumulation of lysosomal membrane. This was accompanied by a significant change in dendritic spine structure, which included a lengthening of dendritic spines, an increase in the number of filipodia, and an overall decrease in spine number. Inhibition of lysosomal function also inhibited wound healing in neurons by preventing lysosomal fusion with the plasma membrane. Neurons were therefore more susceptible to injury. Our findings suggest that dysfunction in lysosomal Ca2+ signalling and lysosomal fusion with the plasma membrane may contribute to the loss of dendritic spines and neurons seen in neurological disorders, such as Niemann-Pick disease type C1, in which lysosomal function is impaired.